Higgsino-like dark matter from sneutrino late decays - Medina, Anibal Damian (2017)
We consider Higgsino-like dark matter (DM) in the Minimal Supersymmetric Standard Model (MSSM) with additional right-handed neutrino chiral superfields, and propose a new non-thermal way of generating the right amount of relic DM via sneutrino late decays. Due to the large DM annihilation cross-section, decays must occur at lower temperatures than the freeze-out temperature Td≪TF,χ˜1 0∼μ/25, implying a mostly right-handed lightest sneutrino with very small Yukawa interactions. In that context, the right amount of Higgsino-like DM relic density can be accounted for if sneutrinos are produced via thermal freeze-in in the early Universe.